c.2 - Kumar, Samir (Chandigarh, 2011)
The present magnum-opus gives comprehensive answers to oft-simmering questions, in the mind of common man. Is is an insight inti the gimmicks and skull-duggery, which is being pursued by the elites in the 'Rajniti'.
Keywords: Political Elite